2012
DOI: 10.1007/s13402-012-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer cells expressing cell surface GRP78 as a marker for reduced tumorigenicity

Abstract: This study demonstrates the significance of cell surface GRP78 in colon cancer, which may be used as a marker for reduced tumorigenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…These results confirm similar findings in head and neck cancer (21), but differ from a study showing that GRP78+ colon cancer cells exhibit reduced tumorigenicity compared to GRP78− cells (44). We attribute differences between these studies to the fact that our work, but not the study of Hardy et al, excluded dead cells during sorting.…”
Section: Discussionsupporting
confidence: 81%
“…These results confirm similar findings in head and neck cancer (21), but differ from a study showing that GRP78+ colon cancer cells exhibit reduced tumorigenicity compared to GRP78− cells (44). We attribute differences between these studies to the fact that our work, but not the study of Hardy et al, excluded dead cells during sorting.…”
Section: Discussionsupporting
confidence: 81%
“…Our results were consistent with previous studies showing that the ER chaperone GRP78 expression contributes to in vitro and in vivo antiapoptotic effects and chemotherapy resistance in many cancers (Booth et al 2012;Chang et al 2012;Hardy et al 2012;Jin et al 2012;Lee 2007). For example, levels of GRP78 in human gastric cancer cells are strongly correlated with taxane-based therapeutic resistance and recurrence of the disease (Yang et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…GRP78 is overexpressed in colon cancer (13,39) and prostate cancer (9). Our studies showed overexpression of GRP78 in pancreatic cancer cell lines and in tumor compared with normal ductal cells (Fig.…”
Section: Triptolide Induces Er Stress In Pancreatic Cancer Cells Via mentioning
confidence: 53%
“…Studies have shown that although the majority of GRP78 resides in the ER lumen, a fraction of it exists as an ER transmembrane protein, with its NH 2 portion in the cytosol. This can directly bind and inhibit the activity of proapoptotic effectors, such as caspase-7 and the BH3-only proapoptotic protein BIK and its downstream target BAX (13,22). It is intriguing that increased expression of GRP78, which is a mechanism that tolerates a low level of chronic ER stress to thrive under suboptimal conditions, not only causes prosurvival robustness but also confers increased chemoresistance (2,…”
mentioning
confidence: 99%